A comparative clinical study of bone density around zirconia implants (ISSA N.Z.I) ) traditionally loaded and those loaded early and gradually. - عيسى, نزيه; عثمان, طرفه (Latakia University Journal -Medical Sciences Series, 2021)
The aim of this study is to compare the early progressive loading and traditional loading on bone density around the (ISSA N.Z.I) implants used to compensate for a single missing tooth. Materials and methods: The research sample consisted of 12 zirconia implants (ISSA N.Z.I) used in the jaws of 6 patients each with a symmetric loss of one tooth. one implant was installed in the missing tooth site and compensated after 3 months, while the compensation was installed on the opposite side early and gradually starting from the first month of implantation, x-rays were performed after (1, 2, 3 months after implantation) and (2, 5, 9, and12 months after permanent crowned ). Bone density around the implants was assessed in three areas (Apical-body-cervical), and average bone density values were taken using the digital imaging camera (Bemems-sensor/vatech) during the observation period. The results did not show statistical function differences between the two loading techniques on zirconia implants (ISSA N.Z.I) compensated for a single tooth, the average bone density around traditionally loaded implants (163.33-153-17-125.5) whereas the bone density around the early gradually loaded implants (166.5-151.17-127.17) in the three regions (cervical-body-Apical) respectively. Conclusion: The progressive early loading technique did not appear - a significant difference in bone density change around implants (ISSA N.Z.I) from the traditional loading method and both methods can be used to compensate for a single tooth.